2016
DOI: 10.1088/0953-8984/28/14/146001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic phase diagram of the helimagnetic spinel compound ZnCr2Se4revisited by small-angle neutron scattering

Abstract: Abstract. We performed small-angle neutron scattering (SANS) measurements on the helimagnetic spinel compound ZnCr 2 Se 4 . The ground state of this material is a multi-domain spin-spiral phase, which undergoes domain selection in a magnetic field and reportedly exhibits a transition to a proposed spin-nematic phase at higher fields. We observed a continuous change in the magnetic structure as a function of field and temperature, as well as a weak discontinuous jump in the spiral pitch across the domain-select… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…therein). SANS (Cameron et al, 2016) has been used to study the field dependence of the multidomain spin spiral phase with particular focus on a spin nematic phase, proposed at higher field (Felea et al, 2012). A continuous change of magnetic structure is observed as a function of field and temperature while a discontinuous jump of the spiral pitch indicates the domain selection field.…”
Section: Properties Of Non-b20 Spiral Magnets As Inferred From Sansmentioning
confidence: 99%
“…therein). SANS (Cameron et al, 2016) has been used to study the field dependence of the multidomain spin spiral phase with particular focus on a spin nematic phase, proposed at higher field (Felea et al, 2012). A continuous change of magnetic structure is observed as a function of field and temperature while a discontinuous jump of the spiral pitch indicates the domain selection field.…”
Section: Properties Of Non-b20 Spiral Magnets As Inferred From Sansmentioning
confidence: 99%
“…The extent of the bond frustration in ZnCr 2 Se 4 (θ CW /T N ∼ 5.2) is high even compared with other spinel structures. Spin fluctuations in ZnCr 2 Se 4 were observed by diffuse magnetic scattering above T N , suggesting a magnetic microdomain phase below 45 K [21,22]. Further studies conducted between the Curie-Weiss and Néel temperatures revealed the presence of negative thermal expansion below 100 K [16,23], shifting of the magnetic resonance line [20], anomalous behavior of eigenfrequencies of phonon modes [16], and deviation from Curie-Weiss behavior [1], making further investigation with muon spin-relaxation measurements attractive.…”
Section: Introductionmentioning
confidence: 99%
“…This may have been because the spinel structure had a high cubic symmetry. The SANS measurements also confirmed the isotropic phase transitions with respect to the field direction in the monocrystalline ZnCr 2 Se 4 spinel [ 11 ]. The observed ρ (T) dependence in Figure 5 means that doping of the ZnCr 2 Se 4 single crystals under study with tantalum did not affect the thermal activation of electrical conductivity.…”
Section: Resultsmentioning
confidence: 68%
“…The values of the second critical field, H c 2 , connected with the breakdown of the conical spin structure, drop rapidly with temperature, suggesting a spin frustration of the re-entrant type [ 2 ]. Low-angle neutron scattering (SANS) measurements showed the absence of any long-range magnetic order in the high-field (spin-nematic) phase, as well as the fact that all observed phase transitions were surprisingly isotropic concerning the field direction [ 11 ].…”
Section: Introductionmentioning
confidence: 99%